of, that, a Legal Review of Medical Emergency that Happened After a Failed Abortion Attempt - Elfan Winoto (Hang Tuah Law Journal, 2020)
Abortion is the fifth highest cause of maternal mortality. Legal abortions are called abortus provocatus medicinalis and those that are illegal are called abortus provocatus criminalis. Indonesian law prohibits abortion except indications of medical emergencies and the consequences of rape. This study aims to determine the legal consequences of someone who failed an abortion and the legal protection of the doctor who treated her. This legal research uses a juridical normative with a conceptual and legislative approach.The results of the perpetrators and those who helped the abortion that caused medical emergencies to be threatened with Criminal Code Article 53. They cannot be convicted if in accordance with professional standards and standard operating procedures. The conclusion and suggestion are the doctor cannot be convicted as a criminal offender or as an assistant to an abortion crime if it can be proven that an abortion is carried out in emergency condition to save mother or fetus and prevent disability. The government needs to make laws that regulate who will carry out safe, qualitative and responsible abortions.